DAPATKAH INDONESIA BEBAS DARI KUTUKAN KOLONIAL? REFLEKSI KRITIS ATAS MP3EI - Noer Fauzi Rachman & Dian Yanuardy (LPPM Universitas PGRI Sumatera Barat, 2014)
This paper seeks to analyze critically the so-called Master Plan for the Acceleration and Expansion of Indonesian Economic Development (MP3EI)— a newly development master plan launched in 2011 during Susilo Bambang Yudhoyono administration. MP3EI introduced some keywords such as